2019
DOI: 10.3389/fvets.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

Trace Mineral Supplementation for the Intestinal Health of Young Monogastric Animals

Abstract: Growth performance and feed efficiency are essential parameters when evaluating profitability of livestock. However, animal performance does not always reflect optimal gut health. Decades of research have supported the theory that improved animal performance such as average daily gain and feed efficiency can be impacted by intestinal health or the ability of the intestinal mucosa to absorb nutrients, but dysfunction may be found when the animal is stressed. Most of the early research focused on enteric infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…The amount of naringin flavonoid was calculated by external calibration of reference standard of naringin and expressed as naringin. Quantification of salicylic derivatives content was made using HPLC (Agilent (Santa Clara, CA, USA), 1260 series, U.S.A.) according to the European Pharmacopoeia Monograph of Willow bark (01/2013:1583) [17]. The amount of salicylic derivatives was calculated by external calibration of reference standard of salicin and expressed as salicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of naringin flavonoid was calculated by external calibration of reference standard of naringin and expressed as naringin. Quantification of salicylic derivatives content was made using HPLC (Agilent (Santa Clara, CA, USA), 1260 series, U.S.A.) according to the European Pharmacopoeia Monograph of Willow bark (01/2013:1583) [17]. The amount of salicylic derivatives was calculated by external calibration of reference standard of salicin and expressed as salicin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, following the hypothesis that it is possible to improve the response of piglets to weaning and to reduce the incidence of post-weaning diarrhea by including phytogenic blends in the diet as an alternative to antimicrobials, the objective of the present study was to evaluate, in weaned piglets, the potential of two plant-based in-feed additives in front of an oral ETEC F4 challenge, analyzing their effects on performance, clinical response, immune system, and gut health. For that, we compared two diets supplemented with different phytogenic blends with a non-supplemented diet and a diet including pharmacological levels of ZnO as a positive control considering its largely known efficacy to prevent post-weaning colibacillosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduced expression of MUC2 in piglets from sows fed a diet with MMHAC could also indicate that nutrients to make mucin could be saved potentially directing more nutrients for the growth of their piglets. Previous studies showed that chelated mineral sources can regulate intestinal inflammatory response ( Liao et al, 2018 ; Shannon and Hill, 2019 ). The intestinal inflammatory response can be caused by various stimuli, such as viral antigen, bacteria invasion, cytokines, stress, and free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn), Manganese (Mn), and Copper (Cu) are essential minerals for the embryonic and fetal development ( Hostetler et al, 2003 ). Previous studies also showed that these trace minerals had key functional involvements in the intestinal immune system ( Shannon and Hill, 2019 ) and muscle growth ( Zhao et al, 2014 ) of pigs. Zinc enhanced intestinal barrier function with improved gene expression of claudin-1 and occludin in broiler chicken ( Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, understanding the functional properties of ingredients and nutrients can improve the likelihood and potential magnitude of positive growth and health responses, while avoiding antagonistic effects when selecting and adding various feed additives to swine diets. [341,342] One of the most interesting but underexplored health promoting components of feed ingredients are the many naturally occurring polyphenolic compounds in feed ingredients. Several phenolic compounds are associated with DF in many plant-based foods and feeds, which have potent antioxidant and reactive oxygen species scavenging properties that provide protection against oxidative damage [369].…”
Section: Functional Ingredients and Nutrientsmentioning
confidence: 99%